Improving Standby Power Management in Buildings: User-centric Design Strategies for Mitigating Human Errors in Standby Power Management and Energy Efficiency - B. Akhoundi; M. Salari (Iranica Journal of Energy and Environment)
The proliferation of electrical and electronic products in modern lifestyles has led to a significant increase in standby power consumption, posing a challenge for energy conservation efforts. In response, this study explores the potential of user-centric design methodologies in addressing standby power management and energy efficiency. By analyzing human error categories and user interaction behavior, the research aims to identify design gaps and develop strategies for mitigating human errors in standby power usage. Through an exploratory and explanatory approach, data gathered from questionnaires provide insights into users' habits, needs, attitudes, and reflections related to standby power consumption. The findings highlight the potential for user-centric approaches to effectively control standby power in connected appliances, paving the road for future advancements in appliance design that prioritize user behavior and preferences. This study offers a novel perspective on standby power management, emphasizing the importance of human error alleviation and user-centric design in achieving energy efficiency goals.